Archdeacon Thomas of Split (1200 – 1268) – A source of early Croatian History - Matijević Sokol, Mirjana (Array, 2007)
The author presents the famous chronicler of the earliest periods of Croatian history, Archdeacon Thomas (1200. – 1268.) of the Split Church. After being schooled in Italy and elected to the position of Split Archdeacon, Thomas became an influential reformer of the city’ s government and institutions, copying Italian models and even placing Italians in important positions. Thomas was the author of a chronicle of the Split Bishops and Archbishops until 1266, which Ivan Lučić Lucius, its first publisher, entitled the “ Historia Salonitana.” The significance of this work lies in the fact that the chronicle incorporates important information about various aspects of Croatia’ s earliest history. Thus, Thomas writes about the arrival of Croats, proposing the so-called Gothic theory of their provenance, and he mentions various Croatian rulers— Trpimir, Branimir, Muncimir, Tomislav, Držislav, Krešimir, and Zvonimir. Aparticularly noteworthy feature of Thomas’ work is that it relies on historical sources, not on myth and legend. “ Historia Salonitana” has been reworked and enlarged by other authors ; the revised work is generally referred to as the “ Historia Salonitana maior.